Obstructive azoospermia: reconstructive techniques and results (Clinics, 2013)
Obstructive azoospermia is a common cause of male infertility and can result from infection, congenital anomalies, or iatrogenic injury. Microsurgical vasal reconstruction is a suitable treatment for many cases of obstructive azoospermia, although some couples will require sperm retrieval paired with in-vitro fertilization. The various causes of obstructive azoospermia and recommended treatments will be examined. Microsurgical vasovasostomy and vasoepididymostomy will be discussed in detail. The postoperative patency and pregnancy rates for surgical reconstruction of obstructive azoospermia and the impact of etiology, obstructive interval, sperm granuloma, age, and previous reconstruction on patency and pregnancy will be reviewed.